Comparison of The Effectiveness of Gel and Spray Hand Sanitizers Against Reducing The Number of Germs on The Palms - Supenah, Pipin; Usdiyanto, Usdiyanto; Misika, Misika (Indonesian Health Journal, 2022)
Maintaining hand hygiene is one of the measures recommended by the Centers for Disease Control and Prevention (CDC) to help prevent infection during the COVID-19 pandemic. Maintaining hand hygiene can use soap and water or other alternatives such as hand sanitizer with an alcohol content of at least 60%. Hand sanitizer is a hand sanitizer that contains alcohol functions to kill microorganisms in the hands quickly and without rinsing. Hand sanitizers generally consist of two types, namely gels and sprays, both of which have their own advantages and disadvantages. This study aimed to determine the decrease in the number of germs on the palms after using gel and spray hand sanitizers, as well as a comparison of the effectiveness of gel and spray hand sanitizers. The research method used is pre-experimental with the research design "One Group Pretest Posttest design" and the examination method uses Total Plate Count (TPC). The study was conducted at the AAK An Nasher microbiology laboratory from June to August 2021. The results of the study obtained that gel and spray hand sanitizers are effective in reducing the number of germs on the palms, but there is no difference in effectiveness in reducing the number of germs on the palms between the use of gel and spray hand sanitizers. Data analysis using paired sample t-test obtained sig value. (0.000<0.050) for the two types of hand sanitizers, it is concluded that both are significantly able to reduce the number of germs on the palms. The results of the independent samples t-test obtained sig values. (0.449>0.050) There needs to be an effective comparison between gel and spray hand sanitizers. Hand sanitizer gel and spray are effective in reducing the number of germs on the palm, but there is no difference in effectiveness in reducing the number of germs on the palm between the use of gel and spray hand sanitizer